Awareness of Surgical and Medical Intensive Care Nurses’ about Alcohol Withdrawal Syndrome and Care Practices - Arpag, Nurgül; Katran, Hamdiye Banu; Haspolat, Ali; Köprülü, Ali Şefik (Addicta: The Turkish Journal on Addictions, 2024)
Alcohol withdrawal syndrome is a significant global health concern affecting individuals with alcohol use disorder, particularly in hospital settings like intensive care units. Early diagnosis and management are crucial but often complicated by symptom overlap with other conditions. This study aims to evaluate the awareness and knowledge of surgical and medical intensive care unit nurses regarding AWS, focusing on risk factor identification, diagnosis, and care practices. A cross-sectional descriptive study was conducted from November 15 to December 01, 2021, involving 112 nurses from public and private hospitals. Data were col- lected via an online questionnaire developed from existing literature, which included demographic questions and a 20-item alcohol withdrawal syndrome awareness scale, where higher scores indicated better aware- ness. Statistical analysis utilized the Kolmogorov–Smirnov test for normality, Mann–Whitney U for two- group comparisons, and Kruskal–Wallis H for multiple-group comparisons. A multivariate generalized linear model assessed the influence of independent variables on alcohol withdrawal syndrome awareness. Nurses scored an average of 9.92 out of 20 on the alcohol withdrawal syndrome awareness scale, indicat- ing moderate knowledge. Significant differences in awareness were noted based on professional experience, intensive care unit type, and prior training. Nurses with 5 or more years of experience and those with specific training in alcohol withdrawal syndrome care exhibited higher awareness levels (p < .05). The study reveals a
Keywords: Addictions to alcohol; alcohol withdrawal syndrome; awareness; nurses; nursing education; patient care